THE USE OF PICTURE SERIES-AIDED LEARNING STARTEGY TO IMPROVE STUDENTS’ WRITING ABILITY; A Case Study - Siti Salisa Fithrijah (Edulitics (Education, Literature, and Linguistics) Journal, 2019)
This research is CAR (Classroom Action Research) conducted in SMP Negeri 1 Lamongan. This research uses picture aided learning startegy to improve students’ writing ability. The subjects of this study are the 28 (twenty eight) students from grade VII. The research was conducted in year 2018-2019. The results shows that picture series-aided learning can improve students’ writing ability. Their average scores increase from 56.86 into 77.87 (21.01 increase points), that can be elaborated as follows: 10.43 points increase, from 20.86 into 31.29, for content; 5.28 points increase, from 11.79 into 17.07, for language; and 5.29 points increase, from 24.21 into 29.50, for organization.